GENDER DIFFERENCES IN ROLE CONFLICT AND ROLE AMBIGUITY ON COMMITMENT TO INDEPENDENCE - Aryanto Aryanto; Agil Novriansa; Muhammad Farhan (AKUNTABILITAS, 2023)
This study aims to empirically examine the impact of role conflict and role ambiguity on commitment to independence by using a gender perspective approach. This study used a survey method. The sample in this study was the local government internal auditor, namely the District/City Government Inspectorate auditor. The results of purposive sampling obtained the number of respondents as many as 124 local government internal auditors who came from 11 Regional Inspectorates in the provinces of the Special Region of Yogyakarta, South Sumatra and East Java. Based on the gender approach, results independent sample t-test indicates that male local government internal auditors report the level of role conflict higher than female local government internal auditors, however they report levels of role ambiguity and commitment to independence the same one. In addition, the results of the SEM-PLS analysis showed that role conflict not related to commitment to independence for male and female local government internal auditors. Role ambiguity negatively related to commitment to independence both for male local government internal auditors and female local government internal auditors.